Three vectors are given by:

a=0i+oj+4.0k
b=3.0i+-3.0j+-1.0k
c=1.0i+2.0j+-1.0k
a) Find a(bxc)
b) Find a(b+c)

To find the value of a(bxc), we need to perform a cross product between vectors b and c first, and then perform a dot product with vector a.

a) Cross product of vectors b and c:
To find the cross product, we use the formula:

bxc = (b2c3 - b3c2)i - (b1c3 - b3c1)j + (b1c2 - b2c1)k

Calculating the cross product:
bxc = ((-3.0)(-1.0) - (-1.0)(2.0))i - ((3.0)(-1.0) - (-1.0)(1.0))j + ((3.0)(2.0) - (-3.0)(1.0))k

This simplifies to:
bxc = (-5.0)i - (-4.0)j + (9.0)k

Next, we can take the dot product of vector a with the result of the cross product (bxc):

a(bxc) = (0i + 1j + 4k) · (-5.0i + 4.0j + 9.0k)

Calculating the dot product:
a(bxc) = (0)(-5.0) + (1)(4.0) + (4)(9.0)

This simplifies to:
a(bxc) = 4.0 + 36.0
a(bxc) = 40.0

Therefore, a(bxc) = 40.0.

b) To find a(b+c), we need to find the sum of vectors b and c first, and then take the dot product with vector a.

Vector b + c:
b + c = (3.0i - 3.0j - 1.0k) + (1.0i + 2.0j - 1.0k)

Combining like terms:
b + c = (3.0i + 1.0i) + (-3.0j + 2.0j) + (-1.0k -1.0k)
b + c = 4.0i - 1.0j - 2.0k

Now, we can take the dot product of vector a with the sum of vectors b and c:

a(b+c) = (0i + 1j + 4k) · (4.0i - 1.0j - 2.0k)

Calculating the dot product:
a(b+c) = (0)(4.0) + (1)(-1.0) + (4)(-2.0)

This simplifies to:
a(b+c) = 0.0 - 1.0 - 8.0
a(b+c) = -9.0

Therefore, a(b+c) = -9.0.

To find the cross product of two vectors, we can use the following formula:

a x b = (aybz - azby)i - (axbz - azbx)j + (axby - aybx)k

where ax, ay, az represent the components of vector a, and bx, by, bz represent the components of vector b.

a) Let's start by finding b x c:

b x c = (-3.0)*(-1.0) - (-1.0)*2.0)i - (3.0*1.0 - (-1.0)*1.0)j + (3.0*2.0 - (-3.0)*1.0)k
= -1.0i - 4.0j + 9.0k

Now, let's find a x (b x c):

a x (b x c) = (0*(-4.0) - 4.0*(-4.0))i - (0*(-9.0) - 4.0*(-1.0))j + (0*(-1.0) - 0*(-4.0))k
= 16.0i + 4.0j + 0k

So, a(b x c) = 16.0i + 4.0j + 0k.

b) Now, let's find a(b + c):

To do this, we first need to find b + c:

b + c = (3.0 + 1.0)i + (-3.0 + 2.0)j + (-1.0 + (-1.0))k
= 4.0i - 1.0j - 2.0k

Next, we can multiply the result by vector a:

a(b + c) = (0*4.0 + 0*(-1.0) + 4.0*(-2.0))i + (0*4.0 + 4.0*(-1.0) + 0*(-2.0))j + (0*4.0 + 0*(-1.0) + 4.0*(-2.0))k
= -8.0i - 4.0j - 8.0k

Therefore, a(b + c) = -8.0i - 4.0j - 8.0k.